Predictive Values of Maternal Serum Levels of Procalcitonin, ESR, CRP, and WBC in the Diagnosis of Chorioamnionitis in Mothers with Preterm Premature Rupture of Membrane - farzaneh Broumand; Siamak Naji; Sharareh Seivani (Mashhad University of Medical Sciences, 2018)
Background: Premature rupture of membrane (PROM) refers to the rupture of fetal membranes at least 1 hour before the onset of labor pain. We aimed to determine the predictive value of maternal serum level of procalcitonin in the early diagnosis of chorioamnionitis in mothers with preterm (PPROM).Methods: In this prospective cohort study, 48 patients with PPROM were selected due to limited financial resources and in accordance with previous similar articles. The study was carried out in Kosar ward of Motahhari Hospital of Urmia, Iran. The inclusion criteria were leaking amniotic fluid, positive nitrazine and fern tests, gestational age of 28-33 weeks, and lack of fetal tachycardia. The exclusion criteria were chronic vascular and congenital heart diseases as well as the use of nonsteroidal anti-inflammatory drugs (NSAIDs). To analyze the data, we used descriptive statistics, Chi-square test (OR), independent t-test, and Pearson in SPSS, version 19.Results: The present study was conducted on 48 pregnant women and their neonates. About 39.6% of the mothers were pathologically infected with chorioamnionitis, while 60.4% of the patients were not infected with the disease. Moreover, 68.8% of the neonates had a five-minute Apgar score of ≥ 7. There was a significant correlation between the mothers' infection with histopathologic chorioamnionitis and neonatal hospitalization in neonatal intensive care unit (P